Handbbok on the right to information act 2005 - Das, P. K. (Delhi, 2005)
This is why the Act of the Right to Information, 2005, forms the shape of special legislation imposing the obligations on every public authority to provide information to the person seeking it. This is unprecedented legislation so far the Act embodies strict and statutory provisions for the implementation in the informative aspects of democratic form of governance. The Act in its infant age can take the same shape as the Constitution of India was in 1950 and then grew and grows for its use and universal application. This generalisation though not simple and pure still it holds necessarily true, because right to information is the product of plenary provisions enshrined in the article 19 which is basic and fundamental rights since 1950. The Supreme Court of India and some High Courts while interpreting some sensitive cases pertaining to fundamental right observed and suggested for enactment of a special law on Right to Information. Taking these aspects in mind this book has been written with a total involvement, dedication and sincerity of the purpose, because it is necessary to understand the practice of right to information as the development of right to information is the development of realistic and participative democratic form of government.
Keywords: Right to information act-2005